Effect of instalation depth and distance of drip emitter on coffee leaf water potential in a tropical soil - Barreto, Carlos Vinícius Garcia; Sakai, Emílio; Arruda, Flávio Bussmeyer; Pires, Regina Célia de Matos; Silva, Emerson Alves da (Coffee Science - ISSN 1984-3909)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; mso-hyphenate:none; font-size:12.0pt; mso-bidi-font-size:10.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:AR-SA; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The objective of this work was to evaluate the performance of different configurations of subsurface drip irrigation (SDI) by measuring coffee (Coffeea arabica L.) leaf water potential. Six treatments of drip irrigation combining two drip emitters spaced at 0.50 and 0.80 m, with three drip placement depths: 0 cm (soil surface), 0.10 m and 0.20 cm. The combined treatments were: T1 (50 – 0), T2 (50 – 10), T3 (50 – 20), T4 (80 – 0), T5 (80 – 10) and T6 (80 – 20). Leaf water potential was measured using a Scholander pressure pump at predawn and during the day. Both surface drip irrigation treatments showed a lower predawn leaf water potential. The treatment that presented better performance with higher water potential values was T2. Another fact observed was that treatments with wider spacing between emitters (T4, T5 and T6) always presentd higher water stress than other treatments, mainly in the period when irrigation was suppressed (June, 25th to September, 14th).